2013
DOI: 10.3797/scipharm.1306-05
|View full text |Cite
|
Sign up to set email alerts
|

Ascorbic Acid for the Safe Use of a Sunscreen Agent: Accumulation of Nano Zinc Oxide and Titanium Dioxide on the Skin

Abstract: ObjectivePhysical UV absorbers such as titanium dioxide or zinc oxide have been found to be highly protective against ultraviolet radiation. Sun protection factor depends on the accumulation of the minerals on the skin. UV-absorbing agents must accumulate within the upper skin layers in order to provide a dense light-absorbing layer and guarantee water resistance. The aim of this work was to increase the skin deposition and efficacy of sunscreens without increasing their skin permeation. The application possib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…oleic acid and glyceryl trioleate) disrupt the stratum corneum lipids, thus enhancing the penetration [21,22,23,24]. Leite-Silva et al [22] reported that the formulation containing paraffin oil acts as a penetration enhancer for zinc oxide nanoparticles which, along with titanium dioxide nanoparticles, normally do not penetrate through the barrier of the stratum corneum [25,26,27,28]. …”
Section: Introductionmentioning
confidence: 99%
“…oleic acid and glyceryl trioleate) disrupt the stratum corneum lipids, thus enhancing the penetration [21,22,23,24]. Leite-Silva et al [22] reported that the formulation containing paraffin oil acts as a penetration enhancer for zinc oxide nanoparticles which, along with titanium dioxide nanoparticles, normally do not penetrate through the barrier of the stratum corneum [25,26,27,28]. …”
Section: Introductionmentioning
confidence: 99%
“…In the past, both titanium dioxide and zinc oxide sunscreens were less preferred due to their chalky, white appearance on application. However, micronization of particles and more recently "nanoparticle" formulations have made TiO 2 sunscreens more popular in recent years [11]. Early studies comparing micronized versions of TiO 2 versus micronized versions of zinc oxide sunscreens concluded that micronized zinc oxide sunscreens were superior as they conferred better protection against longer wave UVA and had greater cosmetic outcomes [12].…”
Section: Efficacy Of Titanium Dioxide Sunscreensmentioning
confidence: 99%
“…TiO 2 was able to penetrate into the vacant hair follicles. 11,[17][18][19][20] Physical UV absorbers like titanium dioxide and zinc oxide have been considered as highly protective agents against UVR. ZnO and TiO 2 combinations are particularly valuable because of their ability to filter both UVA and UVB radiations, providing broader UVR protection than that observed with individual component.…”
Section: Introductionmentioning
confidence: 99%